Effect of a physical rehabilitation program with therapeutic massage for men with piriforms muscle syndrome (40 - 50) - Darwish Ahmed, Hossam (International Journal of Psychosocial Rehabilitation, 2024)
Background: Piriforms syndrome is a neuromuscular condition characterized by hip and buttock pain. This syndrome is often overlooked in clinical settings because its presentation may be similar to that of lumbar radiculopathy, primary sacral dysfunction, or innominate dysfunction. The ability to recognize piriforms syndrome requires an understanding of the structure and function of the piriforms muscle and its relationship to the sciatic nerve. Methods two experimental groups of (5) cases suffering from pain of the musculoskeletal syndrome and they were rehabilitated until the dynamic range was restored and the angle of the hip rotation was restored to the inside and outside and improved step, balance and muscular compatibility in a short period RESULTS: The chief investigator demonstrated excellent effect on the measurements. Restoring elasticity, improving the motor range and restoring the angle of hip rotation inside and outside, patient's return to normal condition rapidly.Conclusions: results confirm that subjective assessment, restoring the thigh angle and , rotation of the inside and outside angle, restoring motor range, , restoring flexibility of piriformis muscle.